2019
DOI: 10.1108/k-07-2018-0415
|View full text |Cite
|
Sign up to set email alerts
|

Optimal green supply-chain model design considering full truckload

Abstract: Purpose Supply chain management (SCM) focuses smart logistics and quality service. Diverse elements such as design, procurement, production and sale policies are the keys to SCM efficiency. Due to worsening environmental pollution in recent years, many businesses, government agencies and consumers have become more aware of greenhouse gases (GHG) emissions. In response, the government has established new environmental regulations to control various GHG, such as CO2 and sulfur dioxide. Therefore, to reduce pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Determined during a case study of coal enterprise of China that various driving mechanisms, i.e., government regulations, enterprise resource capability, and supply chain aid the global industries to reach to the green innovation. Te authors Teir research contribution in the context of GSCP strategy [63] Developed a multiobjective decision making hierarchical model, which included the forward and reverse logistic practices. Te model is used to optimize and reduce the recycling as well as manufacturing cost.…”
Section: Literature Surveymentioning
confidence: 99%
“…Determined during a case study of coal enterprise of China that various driving mechanisms, i.e., government regulations, enterprise resource capability, and supply chain aid the global industries to reach to the green innovation. Te authors Teir research contribution in the context of GSCP strategy [63] Developed a multiobjective decision making hierarchical model, which included the forward and reverse logistic practices. Te model is used to optimize and reduce the recycling as well as manufacturing cost.…”
Section: Literature Surveymentioning
confidence: 99%
“…Financial performance may also be achieved by recycling and reusing materials instead of discarding them [69]. This helps the organisation to purchase materials that are not only environmentally friendly but also recyclable [81,82], thus improving the financial performance of the establishment.…”
Section: Performancementioning
confidence: 99%
“…The major concept of variable production rate, which lies in between a certain maximum and minimum limit of the production rate, is utilized from the study by Sarkar et al [6]. It was ultimately proved by Glock [30] and Sarkar et al [31] that the flexibility of PS can reduce defective items. However no other studies have concluded that by utilizing flexible PS, the CE can also be controlled.…”
Section: Flexible Production Ratementioning
confidence: 99%